Dual Catalysis for the Aerobic Oxidation of Benzyl Alcohols – Nitric Acid and Fluorinated Alcohol. Issue 3 (20th December 2016) - Možina, Štefan; Stavber, Stojan; Iskra, Jernej
Abstract : Benzyl alcohols were oxidized with oxygen to aldehydes in excellent yields with high selectivities at room temperature. Dual catalysis was operative with HNO3 as the oxidant and precursor of the nitrogen oxides and with the use of 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol as a template catalyst and solvent. Fluorinated alcohols also increased the selectivity by inhibiting further oxidation to benzoic acids. Activation of nitric acid catalyzed aerobic oxidation by the fluorinated solvent made the use of 2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl (TEMPO) or a metal catalyst superfluous. Abstract : Benzyl alcohols are oxidized with oxygen to aldehydes in excellent yields with high selectivities at room temperature with HNO3 as the catalyst and 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol (HFIP) as a template catalyst. The latter also inhibits further oxidation to benzoic acids.